A STUDY OF ISOLATION AND BIODIVERSITY OF MARINE YEASTS IN ARABIAN SEA - SAVITHA K. KOILERY; T.R. KEERTHI (International Journal of Pharma and Bio Sciences, 2012)
This study represents the isolation and biodiversity of marine yeasts from 200-1000m depth ranges in the coastal regions of Arabian Sea. 109 strains were isolated from sea water and sediments using YM Broth containing Chloramphenicol (0.01%) and Streptomycin (0.002%) and their morphological, physiological and biochemical aspects were characterized. Candida was found to be the major genera (41.29%) followed by Debaryomyces (17.43%), Pichia (12.84%), Rhodotorula (11.01%), Trichosporon (9.17%) and Cryptococcus (8.26%). In both samples at 200-1000m depth regions Candida was the dominant genera. Among the yeasts isolated, oxidative forms were highly predominant (95.41%) and the urease producing forms were comparatively low (26.61%). The marine yeasts were examined for their hydrolytic enzyme production mainly amylase, gelatinase and lipase. The results showed that majority of the isolates had lipolytic potential. In Arabian Sea, Shannon-wiener diversity (H’ (log2)), Peilou’s evenness (J’) and Species richness (d) were found to be higher at 500m depth region.